2006
DOI: 10.1161/circulationaha.106.627430
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment With Anti-CD3 Antibody Reduces the Development and Progression of Atherosclerosis in Mice

Abstract: Background-Atherosclerosis is a chronic inflammatory disease of the large arteries that is the primary cause of heart disease and stroke. Anti-CD3-specific antibodies suppress immune responses by antigenic modulation of the CD3 antibody/T-cell receptor complex. Their unique capacity to restore self-tolerance in a mouse model of diabetes and, importantly, in patients with recent-onset type 1 diabetes involves transforming growth factor-␤-dependent mechanisms via expansion and/or activation of regulatory T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 44 publications
1
56
0
1
Order By: Relevance
“…To further substantiate the role of endogenous Treg cells in postischemic neovascularization, we also treated CD28-deficient mice with nonmitogenic anti-CD3 monoclonal antibody to upregulate endogenous Treg cell levels. 21,22 Finally, we analyzed the proangiogenic potential of exogenous Treg cell administration in Rag1-deficient mice with hindlimb ischemia.…”
mentioning
confidence: 99%
“…To further substantiate the role of endogenous Treg cells in postischemic neovascularization, we also treated CD28-deficient mice with nonmitogenic anti-CD3 monoclonal antibody to upregulate endogenous Treg cell levels. 21,22 Finally, we analyzed the proangiogenic potential of exogenous Treg cell administration in Rag1-deficient mice with hindlimb ischemia.…”
mentioning
confidence: 99%
“…When given after 13 wk of diet, there was 71% less progression over 11 wk. The antibody used was engineered to be missing the Fc portion and so was not pro-inflammatory (1677 NS TAP1 (transporter associated with antigenic processing 1) had no effect on atherosclerosis (932). TAP1 transports cytosol-derived antigens into the ER to be loaded onto MHCI which presents antigen to the TCR with the CD8 adapter (expressed on CTL)…”
Section: Cd3mentioning
confidence: 99%
“…Steffens et al (44) showed that administration of a nonmitogenic anti-CD3 antibody reduced plaque development and markedly inhibited lesion progression in mice with already-established atherosclerosis. This was associated with the induction of a regulatory immune response as revealed by increased production of TGF-b and enhanced expression of Foxp3 in lymph node and spleen cells, respectively.…”
Section: Modulation Of Adaptive T Cell Immunity To Treat In Atherosclmentioning
confidence: 99%